2014
DOI: 10.3233/bme-130801
|View full text |Cite
|
Sign up to set email alerts
|

The Pulse Wave Analysis of Normal Pregnancy: Investigating the Gestational Effects on Photoplethysmographic Signals

Abstract: Objective: Normal pregnancy is associated with profound alterations in the maternal cardiovascular system and PPG represents a sensitive and convenient technique capable of tracking changes in the pulsatile function of arteries. The aim of this study was to investigate the effects of maternal cardiovascular alterations on the finger tip photoplethysmography (PPG) during normal gestation. Methods: Thirty five healthy pregnant women were studied at each trimester of pregnancy and again on gestational age using P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…The increased PAI, which is an indicator of wave reflection, its trend was consistent with the results of augmentation index (AIx) obtained from the pulse pressure using applanation tonometry as an indicator of wave reflection within the arterial tree [ 11 ]. In some research, the PAI can measure the morphological changes by PPG signal.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The increased PAI, which is an indicator of wave reflection, its trend was consistent with the results of augmentation index (AIx) obtained from the pulse pressure using applanation tonometry as an indicator of wave reflection within the arterial tree [ 11 ]. In some research, the PAI can measure the morphological changes by PPG signal.…”
Section: Discussionsupporting
confidence: 81%
“…Photoplethysmography (PPG) is an optical measurement technique which be used in the microvascular bed of tissue, wave reflections and arterial stiffness can be measured noninvasively using PPG signals which reflect the changes in blood volume with each heart beat, because arterial pulsations are the most significant portion of PPG. PPG’s oscillating component provides a pulsatile wave, whose contour may include content descriptive of vascular health [ 11 ]. It is possible to assess, through pulse contour variations, the cardiovascular activities, including wave reflections and arterial stiffness, as the measure of profound alterations in the cardiovascular system of the DOC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of normal hemodynamic adaptation to pregnancy have shown decreased TVR and increased arterial compliance, detectable already at five weeks of gestation (17,42). Previous research with PWA starting in the late first trimester, have shown a decrease in arterial stiffness, expressed as AIx or PPG indices, reaching a nadir in the second trimester, and then increasing toward the end of pregnancy (18)(19)(20)(21)(22). In a study with preconceptional comparisons in spontaneous conceptions, reduced AIx was found already at six gestational weeks (43).…”
Section: Discussionmentioning
confidence: 96%
“…A slight increase in TVR is then seen towards term (15). In accordance with TVR changes, arterial stiffness parameters show a U-shaped relation to gestational age (19)(20)(21)(22), but studies in very early gestation and studies using DPA in pregnancy are scarce.…”
Section: Introductionmentioning
confidence: 98%
“…Thus accurate interpretation of pulse wave is of great significance. In recent years, work on how to quantify the state of the cardiovascular system from the parameters of pulse wave has been reported [2][3][4][5][6], one of which is to change the working condition of cardiovascular system by taking exercise, and study the variability of the pulse wave. A. Figueroa studied the influence of acute exercise with whole-body vibration on wave reflection and leg arterial stiffness [4].…”
Section: Introductionmentioning
confidence: 99%